2015
DOI: 10.1007/s12275-015-4616-4
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal wall teichoic acid is required for the pathogenesis of Streptococcus pneumoniae in murine models

Abstract: Pneumococcal asymptomatic colonization of the respiratory tracts is a major risk for invasive pneumococcal disease. We have previously shown that pneumococcal wall teichoic acid (WTA) was involved in pneumococcal infection of sepsis and adherence to epithelial and endothelial cells. In this study, we investigated the contribution of pneumococcal WTA to bacterial colonization and dissemination in murine models. The result showed that nasopharynx colonizing D39 bacterial cells have a distinct phenotype showing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…It was suggested that the three LCP proteins attach CPS and TA polymers to PGN, and that the LCP enzymes are required to form the LTA 19 . However, another protein, RafX (SPD_1672 in strain D39, SP_1893 in strain TIGR4), has been proposed to assemble pnWTA based on the reduced amount of WTA detected by an antibody in RafX-deficient strains, which also showed impaired colonization capabilities, growth defects, and attenuation in virulence 20 , 21 .…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that the three LCP proteins attach CPS and TA polymers to PGN, and that the LCP enzymes are required to form the LTA 19 . However, another protein, RafX (SPD_1672 in strain D39, SP_1893 in strain TIGR4), has been proposed to assemble pnWTA based on the reduced amount of WTA detected by an antibody in RafX-deficient strains, which also showed impaired colonization capabilities, growth defects, and attenuation in virulence 20 , 21 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, inoculation might initially produce a localized infection at the site of inoculation, followed by localized organ infection or generalized sepsis. 52,72,102,106 In all cases, the maximal severity of disease that is necessary to achieve the scientific goals should be delineated. For example, a study that focused on sepsis might require the most severe degree of disease, whereas the least severe stage of infection might be sufficient for studies that focused on colonization.…”
Section: Identifying and Implementing Endpoints For Geriatric Micementioning
confidence: 99%